Pertunjukan Keruncong Stambul Fajar Sebagai Simbol Sejarah - Saputra, Iqbal H. (TAMUMATRA, 2018)
Stambul was introduced in Kota Pelabuhan Surabaya the late nineteenth century, until the early twentieth century. Stambul Music is part of a drama performance, the music accompaniment nuanced typical of Stambul, a variation of keroncong music. Keruncong Stambul Fajar in Mendanau Island, Belitung Regency, Bangka-Belitung Islands Province, has the same roots of the arts. Keruncong Stambul Fajar Pulau Mendanau is one form of artifacts, of the many artifacts in Belitung Island. This basic rhythmic music is a proof that the assimilation and alkuturation of Belitong Island has long been happening, as it has been in other parts of the archipelago, in different variants and forms. The problems studied in this paper are: 1) How can the Stambul musicÂ  get to Belitung Island ?; 2) What is the concrete proof of cultural intercrops which then gave birth to assimilation and acculturation in music art Stambul Fajar Pulau Mendanau, Bangka Belitung Islands province with the same art, both spread in the archipelago, as well as those in the area of origin?Â